Metodologi Studi Tasawuf: Wahdatul Wujud Hamzah Fansuri - Sri Suyanta; Arizul Suwar; Dahri Dahri (Tadabbur: Jurnal Peradaban Islam, 2022)
Humans cannot be understood through their outward aspects (eksoteric), so also religion. if humans consist of the dimensions of the soul and body then religion also consists of the outer and inner dimensions, also called the spiritual dimension which in Islam is known as tasawuf. This article aims to describe the Sufism approach in Islamic studies that focuses on the wahdatul wujud of Hamzah Fansuri thought. Hamzah Fansuri is known as the first Sufi to introduce the doctrine of wahdatul wujud in the Archipelago. The teachings of wahdatul wujud focus on the process of defeating the ego (negating oneself) through self-purification, by imitating God's character as much as possible so that it can reach the stage of perfection called insan kamil. This research is a literature study that utilizes various relevant references using descriptive analysis methods. The results of this study say that the process of the journey of the human soul from beginning to end according to Hamzah Fansuri can be concluded with the process of tajalli and taraqqi through certain stages.